Phosphorus-Sulfur Heterocycles Incorporating an O-P(S)-O or O-P(S)-S-S-P(S)-O Scaffold: One-Pot Synthesis and Crystal Structure Study - Hua, Guoxiong (Molecules, 2017)
A new one-pot preparative route was developed to synthesize novel organophosphorus-sulfur heterocycles via the reaction of the four-membered ring thionation reagent [2,4-diferrocenyl-1,3,2,4-diathiadiphosphetane 2,4-disulfide (FcLR, a ferrocene analogue of Lawesson’s reagent)] and alkenyl/aryl-diols and I(2) (or SOCl(2)) in the presence of triethylamine. Therefore, a series of five- to ten-membered heterocycles bearing an O-P(S)-O or an O-P(S)-S-S-P(S)-O linkage were synthesized. The synthesis features a novel application of the multicomponent reaction, providing an efficient and environmentally benign method for the preparation of the unusual phosphorus-sulfur heterocycles. Seven representative X-ray structures confirm the formation of these heterocycles.